A multi-ion doped pre-lithiated silicon-oxygen material and preparation method thereof

By doping magnesium and copper in prelithiated silicon oxygen materials and combining liquid phase prelithiation and vapor deposition treatment, a nitrogen-containing amorphous carbon deposition layer is formed, which solves the structural stability deviation and high electron impedance of existing materials. The problem of this achieves high specific capacity, high first-time efficiency and excellent processing performance.

CN116053440BActive Publication Date: 2025-02-11ZHEJIANG LICHEN NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310084851.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-09
Publication Date
2025-02-11
Estimated Expiration
2043-02-09

AI Technical Summary

Technical Problem

The existing prelithiated silicon oxygen materials have problems such as structural stability deviation, high electronic impedance, low first-time efficiency and poor processing performance in lithium-ion batteries.

Method used

采用多离子掺杂预锂化硅氧材料的制备方法,通过将镁粉和铜粉掺杂到氧化亚硅中,并通过液相预锂化处理,形成镁铜掺杂纳米硅复合材料,随后进行气相沉积法处理,形成含氮无定形碳沉积层,降低电子阻抗。

Benefits of technology

It improves the structural stability, circulation and power performance of the material, improves specific capacity, first-time efficiency and processing performance, and ensures the excellent performance of the material in lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116053440B_ABST
    Figure CN116053440B_ABST
Patent Text Reader

Abstract

The present invention provides a multi-ion doped pre-lithiation silicon-oxygen material and a preparation method thereof, comprising the following steps: grinding silicon dioxide and magnesium copper powder to obtain material A; adding lithium sheets to an ether-containing solution, and adding lithium borate to obtain a boron-containing pre-lithiation solution B; then adding powder material A to solution B for pre-lithiation; and finally coating nitrogen-containing amorphous carbon on its surface by vapor deposition to obtain a multi-ion doped pre-lithiation silicon-oxygen material. The composite material improves the electronic conductivity of the material by copper doping and forms magnesium silicate by magnesium doping, which has good stability, and exerts the synergistic effect between the two elements to improve the cycle and power performance of the composite material; and combines the liquid phase pre-lithiation of the material to improve the pre-lithiation depth and integrity of the material. The composite material prepared by the composite material has the characteristics of high first efficiency, good power performance, excellent cycle performance, etc. when applied to lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion battery material preparation, in particular to a multi-ion doped pre-lithiated silicon oxide material and a preparation method thereof. Background Art

[0002] Pre-lithiation treatment is a method to improve the performance of negative electrode materials for lithium-ion batteries. It can embed lithium into lithium silicate formed in silicon oxide SiOx materials in advance, such as Li4SiO4, Li2SiO3, and Li2Si2O5, to avoid the consumption of active lithium in the positive electrode and effectively improve the first coulombic efficiency of silicon oxide. However, Li4SiO4 formed by negative electrode materials in the prior art is easily soluble in water, and excess metallic lithium will cause high alkalinity, affecting the structural stability and processing performance of the material, and causing a large number of bubbles to be generated during the slurrying process, making the slurrying and coating process very difficult.

[0003] Some existing technologies reduce the degree of pre-lithiation and the amount of residual alkali by metal doping, and at the same time form a stable silicate structure, thereby improving the cycle and other performance. For example, the patent document with patent application number CN202110442399.9 discloses a pre-lithiation silicon-oxygen composite material, a precursor, and its preparation method and application. The core of the pre-lithiation silicon-oxygen composite material precursor is successively coated by an intermediate layer and an outer shell. The core and the intermediate layer are pre-lithiation silicon-oxygen materials, and the intermediate layer is distributed with Li2SiO3, and the outer shell is distributed with TiO2. There is no other layer structure between the intermediate layer and the outer shell. In this patented technical solution, the lithium silicate salt in the pre-lithiation silicon-oxygen composite material is isolated from water, so that even if the composite material is homogenized for a long time, the pH value of the slurry hardly changes. However, this technical solution has the problem of deviation in the structural stability of the material, and it is prone to risks such as diving during the later cycle. At the same time, the electronic impedance of the material has not improved, affecting the power performance. Therefore, it is necessary to develop a pre-lithiation silicon oxide material with excellent processing performance, low electronic impedance, high specific capacity, high first efficiency and stable structure, so as to improve the material's processing performance such as slurry coating and its cycle, power and other performance. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a method for preparing a multi-ion doped pre-lithiated silicon oxide material.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a multi-ion doped pre-lithiated silicon-oxygen material, characterized in that it comprises the following steps:

[0007] (1) Mixing magnesium powder and copper powder in proportion to obtain mixed metal powder; then mixing silicon oxide and the mixed metal powder in proportion, adding a solvent, and obtaining a magnesium-copper doped nano-silicon composite material after ball milling and drying; wherein silicon oxide: magnesium powder: copper powder = 100: (1-10): (0.5-2); the magnesium powder and copper powder can be simply mixed by grinding, stirring, etc., or a certain alloy structure can be formed at the interface of the magnesium powder and the copper powder by ball milling, etc.;

[0008] (2) adding lithium flakes to an ether-containing solution, stirring the solution thoroughly, and then adding lithium borate to the ether-containing solution, and dispersing the solution uniformly to obtain a boron-containing pre-lithiation solution; wherein the ratio of lithium flakes: ether-containing solution: lithium borate is (1-10): 100: (0.5-2);

[0009] (3) adding the magnesium-copper doped nano-silicon composite material obtained in step (1) to the boron-containing pre-lithiation solution obtained in step (2) in a mass ratio of 100:(5-20) to carry out a pre-lithiation reaction, wherein the pre-lithiation temperature is 25-100° C. and the pre-lithiation time is 10-120 min; after the pre-lithiation is completed, filtering, washing and drying the solid to obtain a pre-lithiation silicon oxide precursor material;

[0010] (4) The pre-lithiation silicon-oxygen precursor material is transferred to a tubular furnace, and an inert gas is first introduced to exhaust the air in the tube. Subsequently, a mixed gas containing a carbon source is introduced and the temperature is raised to 700-1100°C for 1-6 hours to form a deposition layer on the surface of the pre-lithiation silicon-oxygen precursor material. Then, the introduction of the mixed gas is stopped, and the material is cooled to room temperature under an inert atmosphere and crushed to obtain a pre-lithiation silicon-carbon composite material.

[0011] Furthermore, the solvent in step (1) is selected from one or more of ethanol, ethylene glycol, propylene glycol, n-butanol, and isobutanol.

[0012] Furthermore, the particle size of the silicon monoxide in step (1) is 0.5 to 2 µm.

[0013] Furthermore, the ether-containing solution in step (2) is selected from one or more of methyl ether, ethyl ether, methyl tert-butyl ether, ethylene glycol pentyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, ethylene glycol monobutyl ether, diethylene glycol propyl ether, and triethylene glycol hexyl ether.

[0014] Furthermore, the mass concentration of the boron-containing pre-lithiation solution B in step (2) is (1.5-12) wt%.

[0015] Furthermore, the carbon source gas in step (4) is selected from one or more of methane, acetylene, ethylene and diazomethane.

[0016] Furthermore, in step (4), the mixed gas also contains ammonia, and the volume ratio of the carbon source to the ammonia is 10:(1-5).

[0017] In the mixed gas used in the present invention, -CH in the carbon source and NH in the nitrogen source are cracked at high temperature to generate free radicals C and N, which are then deposited on the surface of the material to form an amorphous carbon deposition layer doped with nitrogen atoms. The nitrogen atoms have one more valence electron than the carbon atoms. After nitrogen is doped into the hexagonal structure of the carbon layer, nitrogen-containing functional groups such as pyridine, pyrrole, graphitic nitrogen, and pyridine oxide can be formed, thereby improving the surface chemical activity of the nano-carbon material and reducing the electronic impedance.

[0018] Furthermore, the heating rate in step (4) is 1 to 10°C / min.

[0019] Another object of the present invention is to provide a multi-ion doped pre-lithiated silicon oxide material prepared by the method, the parameters of the multi-ion doped pre-lithiated silicon oxide material are: specific capacity ≥1350mAh / g, first efficiency ≥92%, pH ≤10.

[0020] The purpose of the present invention also includes providing the use of the above-mentioned multi-ion doped pre-lithiated silicon oxide material in lithium batteries.

[0021] The application of the technical solution of the present invention can achieve the following beneficial effects:

[0022] 1) Summary of the scheme of the present invention: Copper doping can improve the electronic conductivity of the material, and magnesium doping forms magnesium silicate with good stability. By exerting the synergistic effect between the two elements, the cycle and power performance of the composite material can be improved;

[0023] 2) Liquid phase pre-lithiation is used to improve the pre-lithiation depth and completeness of the material, thereby improving the initial efficiency of the material. At the same time, the outer coating layer is nitrogen-containing amorphous carbon, and nitrogen atom doping reduces the electronic impedance of the material and improves the power performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a SEM image of the pre-lithiated silicon-carbon composite material prepared in Example 1; DETAILED DESCRIPTION

[0025] Example 1

[0026] A method for preparing a multi-ion doped pre-lithiated silicon-oxygen material comprises the following steps:

[0027] (1) 5 g of nano magnesium powder and 1 g of nano copper powder were mixed and ball-milled to obtain a mixed metal powder; then 100 g of silicon oxide (1 µm) and 6 g of the mixed metal powder were added to a ball mill and mixed evenly, and 500 ml of ethylene glycol solvent was added, ball-milled, and vacuum-dried at 80 °C for 24 h to obtain a magnesium-copper doped nano silicon composite material A;

[0028] (2) Add 5 g of lithium flakes to 100 ml of methyl ether solution, stir thoroughly, add 1 g of lithium borate, and disperse evenly to obtain a boron-containing pre-lithiation solution B with a mass concentration of 6 wt%;

[0029] (3) adding 100 g of composite material A to 150 g of solution B for pre-lithiation reaction, the pre-lithiation temperature is 50° C., and the pre-lithiation time is 60 min; then filtering, washing the solid with propylene carbonate and drying at 80° C. to obtain a pre-lithiation silicon oxide precursor material;

[0030] (4) The pre-lithiated silicon-oxygen precursor material is then transferred to a tubular furnace by a vapor deposition method. First, argon inert gas is introduced to exhaust the air in the tube, and a mixed gas of methane and ammonia (methane: ammonia = 10:3) is introduced. The temperature is increased to 950°C at a heating rate of 5°C / min and maintained for 3 h. Then, the introduction of the mixed gas is stopped, and the material is cooled to room temperature under an argon inert atmosphere and crushed to obtain a pre-lithiated silicon-carbon composite material.

[0031] Example 2

[0032] A method for preparing a multi-ion doped pre-lithiated silicon-oxygen material comprises the following steps:

[0033] (1) 1 g of nano magnesium powder and 0.5 g of nano copper powder were mixed and ball-milled to obtain a mixed metal powder; then 100 g of silicon oxide (0.5 µm) and 1.5 g of the mixed metal powder were ball-milled and mixed, and 500 ml of ethanol solvent was added, ball-milled, and vacuum-dried at 80 ° C for 24 h to obtain a magnesium-copper doped nano silicon composite material A;

[0034] (2) Add 1 g of lithium flakes to 100 ml of methyl tert-butyl ether solution, stir thoroughly, add 0.5 g of lithium borate, and disperse evenly to obtain a boron-containing pre-lithiation solution B with a mass concentration of 1.5 wt%;

[0035] (3) adding 100 g of composite material A to 333 g of solution B for pre-lithiation reaction, the pre-lithiation temperature is 25° C., and the pre-lithiation time is 120 min; then filtering, washing the solid with propylene carbonate and drying at 80° C. to obtain a pre-lithiation silicon oxide precursor material;

[0036] (4) The pre-lithiated silicon-oxygen precursor material is then transferred to a tubular furnace by a vapor deposition method. First, argon inert gas is introduced to exhaust the air in the tube, and a mixed gas of acetylene and ammonia (acetylene: ammonia = 10:1) is introduced. The temperature is increased to 700°C at a heating rate of 1°C / min and maintained for 6 h. Then, the introduction of the mixed gas is stopped, and the material is cooled to room temperature in an argon inert atmosphere and crushed to obtain a pre-lithiated silicon-carbon composite material.

[0037] Example 3

[0038] A method for preparing a multi-ion doped pre-lithiated silicon-oxygen material comprises the following steps:

[0039] (1) 10 g of nano magnesium powder and 2 g of nano copper powder were ball-milled to obtain a mixed metal powder; then 100 g of silicon oxide (2 µm) and 12 magnesium copper alloy were mixed in a certain proportion, 500 ml of n-butanol solvent was added, ball-milled, and vacuum-dried at 80 °C for 24 h to obtain a magnesium-copper doped nano silicon composite material A;

[0040] (2) Add 10 g of lithium flakes to 100 ml of triethylene glycol monobutyl ether solution, stir thoroughly, add 2 g of lithium borate, and disperse evenly to obtain a boron-containing pre-lithiation solution B with a mass concentration of 12 wt%;

[0041] (3) adding 100 g of composite material A to 166.67 g of solution B for pre-lithiation reaction, the pre-lithiation temperature is 100 ° C, and the pre-lithiation time is 10 min; then filtering, washing the solid with propylene carbonate and drying at 80 ° C to obtain a pre-lithiation silicon oxide precursor material;

[0042] (4) The pre-lithiated silicon-oxygen precursor material is transferred to a tubular furnace by a vapor deposition method. First, argon inert gas is introduced to exhaust the air in the tube, and a mixed gas of ethylene and ammonia (ethylene: ammonia = 10:5) is introduced. The temperature is increased to 1100°C at a heating rate of 10°C / min and maintained for 1 h. Then the introduction of the mixed gas is stopped, and the material is cooled to room temperature in an argon inert atmosphere and crushed to obtain a pre-lithiated silicon-carbon composite material.

[0043] Comparative Example

[0044] 100 g of nano-silicon powder was added to 150 g of solution B prepared in Example 1 for pre-lithiation reaction at a reaction temperature of 50°C for 60 min; the mixture was then filtered, washed with propylene carbonate, and dried at 80°C to obtain a pre-lithiated silicon-oxygen precursor material; the mixture was then carbonized at 800°C for 3 h using a vapor deposition method with methane as the carbon source, and then the methane gas was stopped, and the mixture was cooled to room temperature in an argon atmosphere and crushed to obtain a pre-lithiated silicon-carbon composite material.

[0045] 1. SEM test:

[0046] Figure 1 This is a SEM image of the pre-lithiated silicon-carbon composite material prepared in Example 1. It can be seen from the figure that the material has a granular structure with a uniform size distribution. The particle size D50 is between 5-10µm, and the white dotted material on the surface is residual lithium.

[0047] 2. Physical and chemical properties of materials and button battery testing:

[0048] The lithium-ion battery pre-lithiation silicon-carbon composite materials obtained in Examples 1 to 3 and the comparative example are respectively assembled into button batteries A1, A2, A3 and B1; the preparation method thereof is: adding a binder, a conductive agent and a solvent to the negative electrode material, stirring to make a slurry, coating it on a copper foil, and drying and rolling it. The binder used is LA136D binder, the conductive agent is SP, the negative electrode material is the negative electrode material prepared in Examples 1 to 3 and the comparative example, the solvent is double distilled water, and the ratio is: negative electrode material: SP: LA136D: double distilled water = 95g: 1g: 4g: 220ml; the electrolyte is LiPF6 / EC+DEC (1:1), the metal lithium sheet is the counter electrode, the diaphragm is polyethylene (PE), polypropylene (PP) or polyethylene propylene (PEP) composite film, the simulated battery assembly is carried out in an argon-filled glove box, the electrochemical performance is carried out on a Wuhan Landian Xinwei 5V / 10mA battery tester, the charge and discharge voltage range is 0.005V to 2.0V, and the charge and discharge rate is 0.1C.

[0049] Specific surface area test method: The specific surface area of ​​the material is tested according to the national standard GBT / 245332019 "Graphite negative electrode materials for lithium-ion batteries". At the same time, the OI value of the powder material is tested by XRD equipment. The element composition is analyzed by EDS. The conductivity of the powder material is tested by a four-probe tester.

[0050] Table 1 shows the test results and physical and chemical performance comparison results of button cells of the embodiment and the comparative example.

[0051] Table 1

[0052]

[0053] As can be seen from Table 1, the discharge capacity and efficiency of the button battery prepared by using the negative electrode materials obtained in Examples 1 to 3 are significantly higher than those in the comparative example. The experimental results show that the negative electrode material of the present invention can make the battery have good discharge capacity and efficiency. The reason is that the nano-silicon material prepared in the embodiment is doped with metal elements with electronic conductivity, and a silicon alloy is formed during the charge and discharge process, which improves the structural stability of the material and improves the cycle performance. At the same time, the high specific surface area and its liquid phase pre-lithiation improve the pre-lithiation depth of the material, improve the gram capacity of the material and its initial efficiency. In addition, the material contains metallic copper, which reduces impedance, thereby improving the kinetic properties of the material (i.e., a lower OI value).

[0054] 3. Soft pack battery test

[0055] The pre-lithiation silicon-carbon negative electrode materials obtained in Examples 1 to 3 and the comparative example and doped with 90% artificial graphite were used as negative electrode materials, the ternary material NCM111 was used as positive electrode material, LiPF6 / EC+DEC (volume ratio 1:1) was used as electrolyte, and Celgard 2400 membrane was used as separator to prepare 5Ah soft-pack batteries C1, C2, C3, D1 and their corresponding negative electrode sheets, and the full-charge rebound of the negative electrode sheets and the cycle performance of the soft-pack batteries were tested.

[0056] 3.1 Full power rebound:

[0057] Test method: Charge the soft-pack battery to 4.2V, then use a micrometer to test the thickness of the fully charged negative electrode plate, and calculate the full charge rebound of the plate. The test results are detailed in Table 2.

[0058] 3.2 Cycle Test

[0059] Test method: voltage range 2.5-4.2V, charge and discharge 1C / 1C, cycle 500 times, test results are shown in Table 2.

[0060] 3.3 Ratio Test

[0061] The battery was fully charged at a rate of 2C, and the ratio of its constant current charging capacity to the constant current and constant voltage charging capacity was tested. The test results are shown in Table 2.

[0062] Table 2

[0063]

[0064] As can be seen from Table 2, the capacity and capacity retention rate of the soft-pack battery prepared by the negative electrode material obtained in Examples 1 to 3 after multiple cycles are higher than those of the comparative example. The reason is that the pre-lithiation silicon-carbon negative electrode material of the present invention is doped with magnesium and copper elements to form a silicon alloy to improve the structural stability of the material, reduce the impedance of the material, and improve the cycle performance. At the same time, amorphous carbon containing nitrogen atoms is used to reduce its impedance, and to increase the transmission rate of lithium ions during charging and discharging, thereby avoiding lithium accumulation and reducing full-charge expansion. At the same time, since the embodiment material has a lower electrode sheet surface resistance and a lower OI value, the constant current ratio capability of the material during rate charging is improved.

[0065] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a multi-ion doped pre-lithiated silicon oxide material, characterized in that: The steps include: (1) Mixing magnesium powder and copper powder in proportion to obtain mixed metal powder; then mixing silicon oxide and the mixed metal powder in proportion, adding a solvent, and obtaining a magnesium-copper doped nano-silicon composite material after ball milling and drying; wherein silicon oxide: magnesium powder: copper powder = 100: (1-10): (0.5-2); (2) adding lithium flakes to an ether-containing solution, stirring the solution thoroughly, and then adding lithium borate to the ether-containing solution, and dispersing the solution uniformly to obtain a boron-containing pre-lithiation solution; wherein the ratio of lithium flakes: ether-containing solution: lithium borate is (1-10): 100: (0.5-2); the ether-containing solution is selected from one or more of methyl ether, ethyl ether, methyl tert-butyl ether, ethylene glycol pentyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, ethylene glycol monobutyl ether, diethylene glycol propyl ether, and triethylene glycol hexyl ether; (3) adding the magnesium-copper doped nano-silicon composite material obtained in step (1) to the boron-containing pre-lithiation solution obtained in step (2) in a mass ratio of 100:(5-20) to carry out a pre-lithiation reaction, wherein the pre-lithiation temperature is 25-100° C. and the pre-lithiation time is 10-120 min; after the pre-lithiation is completed, filtering, washing and drying the solid to obtain a pre-lithiation silicon oxide precursor material; (4) The pre-lithiation silicon-oxygen precursor material is transferred to a tubular furnace, and an inert gas is first introduced to exhaust the air in the tube, and then a mixed gas containing a carbon source and ammonia is introduced, wherein the volume ratio of the carbon source to ammonia is 10:(1-5), and the temperature is raised to 700-1100°C for 1-6 hours to form a deposition layer on the surface of the pre-lithiation silicon-oxygen precursor material. Then, the introduction of the mixed gas is stopped, and the temperature is lowered to room temperature under an inert atmosphere, and the material is crushed to obtain a pre-lithiation silicon-carbon composite material.

2. The method for preparing a multi-ion doped pre-lithiated silicon oxide material according to claim 1, characterized in that: The solvent described in step (1) is selected from one or more of ethanol, ethylene glycol, propylene glycol, n-butanol, and isobutanol.

3. The method for preparing a multi-ion doped pre-lithiated silicon oxide material according to claim 1, characterized in that: The particle size of silicon monoxide in step (1) is 0.5 to 2 µm.

4. The method for preparing a multi-ion doped pre-lithiated silicon oxide material according to claim 1, characterized in that: The mass concentration of the boron-containing pre-lithiation solution described in step (2) is (1.5-12) wt%.

5. The method for preparing a multi-ion doped pre-lithiated silicon oxide material according to claim 1, characterized in that: The carbon source gas in step (4) is selected from one or more of methane, acetylene, ethylene and diazomethane.

6. The method for preparing a multi-ion doped pre-lithiated silicon oxide material according to claim 1, characterized in that: The rate of the heating process in step (4) is 1 to 10°C / min.

7. The multi-ion doped pre-lithiated silicon-oxygen material prepared by the method according to any one of claims 1 to 6, characterized in that: The parameters of multi-ion doped pre-lithiated silicon oxide materials are: specific capacity ≥1350mAh / g, first efficiency ≥92%, pH ≤10.

Citation Information

Patent Citations

  • Pre-lithiated silicon-oxygen composite materials, precursors, their preparation methods and applications

    CN113193181B

  • Negative electrode composite material with multilayer core-shell structure and preparation method and application thereof

    CN110556529A

  • Pre-lithiated negative electrode material as well as preparation method and application thereof

    CN114709389A